Tick-borne diseases: an update for general practice. (2nd March 2020) - Graham, Sharon
Abstract : Practice nurses offering pre-travel consultations should be aware of tick-borne diseases. Sharon Graham outlines how to help prevent these diseases in travellers Ticks are the vectors for a number of bacterial and viral infections that can affect humans. This article will outline the general transmission, risk and prevention of tick-borne diseases. Many of these diseases are associated with travel outside of the UK. Where a vaccine for a disease is available in the UK, information will be provided, but not all tick-borne disease is vaccine preventable and people should be aware of personal protection and bite avoidance measures.